Range extension of the threatened Red Crossbill (Loxia curvirostra percna) in Canada: new insights from Anticosti Island, Québec - Junior A. Tremblay; Michel Robert; Douglas P. Hynes; Matthew A. Young; Bruno Drolet (Avian Conservation and Ecology, 2018)
Red Crossbill (Loxia curvirostra percna; e.g., Type 8) is considered a distinctive taxonomic group likely restricted to the island of Newfoundland. Although it has been speculated that the percna subspecies may be extinct, recent works continue to show that Red Crossbills from insular Newfoundland are morphologically and vocally distinct. Large-billed Red Crossbills that may be percna have been observed outside Newfoundland and these sightings are likely due to movements of birds to the mainland during times of food shortages in their core range of occurrence. Red Crossbills had been previously detected on Anticosti Island, in 1963 and in the 1980s, but subspecies or vocal type identification was not attempted at that time. In recent years, regular sightings of large-billed Red Crossbills have been reported annually on Anticosti Island. Our main objectives with this study were to find Red Crossbills on Anticosti Island to (1) confirm the presence of percna by collecting vocal and morphological data, and (2) determine habitat associations of observed Red Crossbills. Morphometric and spectrographic analyses confirmed that some of the Red Crossbills present on Anticosti during our study were percna. Our results also suggest that the island may support breeding individuals of percna, which has direct consequences for the species' recovery capability, because it would increase the known population of this threatened species.